2012
DOI: 10.1128/jcm.00662-12
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Single-Step Duplex PCR for Simultaneous Detection of Fasciola hepatica and Fasciola gigantica (Family Fasciolidae, Class Trematoda, Phylum Platyhelminthes)

Abstract: A single-step multiplex PCR (here referred to as a duplex PCR) has been developed for simultaneous detection and diagnosis of Fasciola hepatica and F. gigantica. These species overlap in distribution in many countries of North and East Africa and Central and Southeast Asia and are similar in egg morphology, making identification from fecal samples difficult. Based on a comparative alignment of mitochondrial DNA (mtDNA) spanning the region of cox1-trnT-rrnL, two species-specific forward primers were designed, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 45 publications
(76 reference statements)
1
34
0
1
Order By: Relevance
“…Such selection is necessary to avoid overlapping among PCR amplicons (Culley et al 2013) which result in ambiguous scoring. Agarose gel electrophoresis can only differentiate 30 bp differences in fragments of less than 300 bp while larger DNA fragment requires larger size differences to be able to score the amplicons unambiguously (Le et al 2012;Liu and Wu 2012;Culley et al 2013). Although multiplex PCR has advantages, the potential disadvantages should also be considered before applying the approach such as selection among different sets of primers and low amplification efficiency because of primer competition (Xu et al 2012).…”
Section: Duplex Pcr For Genotyping Kopyor Coconut Accessionsmentioning
confidence: 99%
“…Such selection is necessary to avoid overlapping among PCR amplicons (Culley et al 2013) which result in ambiguous scoring. Agarose gel electrophoresis can only differentiate 30 bp differences in fragments of less than 300 bp while larger DNA fragment requires larger size differences to be able to score the amplicons unambiguously (Le et al 2012;Liu and Wu 2012;Culley et al 2013). Although multiplex PCR has advantages, the potential disadvantages should also be considered before applying the approach such as selection among different sets of primers and low amplification efficiency because of primer competition (Xu et al 2012).…”
Section: Duplex Pcr For Genotyping Kopyor Coconut Accessionsmentioning
confidence: 99%
“…To date, various diagnostic techniques have been developed, including molecular techniques such as PCR, facilitating the identification and discrimination of Fasciola spp. in areas in which F. gigantica and F. hepatica coexist (7,8). Recently, evaluation of field-collected stools samples from ruminants and humans by duplex PCR revealed that this method is sensitive and is able to identify Fasciola spp.…”
mentioning
confidence: 99%
“…Knowledge of these genomic sequences would be of great interest in future studies to determine new detection and quantification methods for this trematode in bivalves, using techniques such as real-time quantitative PCR. No such tools currently exist for the genus Bacciger, although PCR detection is available for various other parasites such as Perkinsus species (Park et al 2005, Abollo et al 2006 or other trematodes (Baba et al 2012, Le et al 2012. Phylogenetic analysis based upon the V4 regions of the 18S gene revealed that species belonging to the Fellodistomidae could be separated into 2 distinct groups.…”
Section: Discussionmentioning
confidence: 99%